Reflections on religion, the divine, and the constitution - Anastaplo, George, 1925-2014 (Lexington Books, 2013)
Connections are suggested among diverse subjects which can remind the reader both of fundamental issues with respect to religion and politics and of the complications of efforts to develop public-policy measures dealing with church/state issues, constitutional applications, and the understanding in the modern world of Life and Death.